Effectiveness of village courts: a study on the four village courts of Narayanganj district - Khan, Md. Mahfuzul Alam (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Governance and Development, 2006.